1994
DOI: 10.1021/ac00079a011
|View full text |Cite
|
Sign up to set email alerts
|

Films Formed by Oxidation of Ferrocene at Platinum Electrodes

Abstract: Oxidation of ferrocene in acetonitrile resulted in films on Pt electrodes under voltammetric conditions. Films were more readily formed with tetrabutylammonium tetrafluoroborate as the electrolyte than with perchlorate salts. No films were detected when ferrocene was oxidized in aqueous 0.05 M cetyltrimethylammonium bromide (CTAB). Analysis of the films by FT-IR and Auger spectroscopy confirmed iron-containing oxidation products on Pt, presumably from chemical reactions of ferricinium ions. Oxidation of 50-100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 33 publications
4
26
0
Order By: Relevance
“…This behavior suggests that the oxidized form of DMFc is not available for re-reduction in acetone. This is in line with similar studies in which ferrocene has been reported to react with acetone, water and alcohols [29].…”
Section: Resultssupporting
confidence: 93%
“…This behavior suggests that the oxidized form of DMFc is not available for re-reduction in acetone. This is in line with similar studies in which ferrocene has been reported to react with acetone, water and alcohols [29].…”
Section: Resultssupporting
confidence: 93%
“…41 Moreover, these observations are similar to those observed for solutions of ferrocene in acetonitrile. 42 cm 2 s -1 , which agreed closely with that determined using cyclic voltammetry. The smaller diffusion coefficient in the RTIL compared to a traditional organic solvent has been reported for various other redox species, including ferrocene and is most likely due the high viscosity of the RTIL solvent.…”
Section: Methodssupporting
confidence: 87%
“…Ferrocene has frequently been used as a redox-active building block in the preparation of a variety of supramolecular assemblies [29] and is attractive from the electrochemical standpoint because it has a wellcharacterized and reversible anodic electrochemistry. However, Rusling and co-workers [30] have shown recently that the oxidation of ferrocene in acetonitrile (at Pt electrodes) yields insoluble films. Another potential complication related to the use of ferrocene as a guest results from the fact that the reported k 0 values for ferrocene cover a rather wide range and seem to correlate, at least partially, with electrode size.…”
Section: Discussionmentioning
confidence: 99%